Making sense of the newspaper crisis: A critical assessment of existing research and an agenda for future work - Siles González, Ignacio (2012)
This article analyzes recent research on the newspaper crisis. It discusses how authors have examined the sources, manifestations, and implications of this crisis, and the proposals to resolve it. In addition, the essay critically examines this body of work by assessing the main spatial and temporal contexts that researchers have studied, the theories and methods that authors employ, and the analytical tropes they have deployed to make sense of the crisis. Building on this assessment of existing research, the article outlines an agenda for future work that fosters an analysis of the process, history, comparative development, and manifold implications of this crisis, and advances various empirical strategies to examine some of its most undertheorized dimensions.